ANALISIS FITOKIMIA DAN AKTIVITAS FARMAKOLOGI TANAMAN KEPEL (Stelechocarpus burahol) TERHADAP BEBERAPA PENYAKIT : REVIEW - Alliza Nur Shadrina; Eva Widyanengsih; Nieda Berliana Eiko; Nirwana Aulia Putri; Nopi Sulastri; Nurliya Dzulfiana; Oktavia Rajebi; Wella Sulvita (Jurnal Buana Farma, 2022)
Kepel fruit (S. burahol) is an empirically well-known Indonesian medicinal plant, especially in the Yogyakarta Palace area. Kepel fruit (S. burahol) is known to have many benefits. Kepel fruit is a plant that has many pharmacologic activities, including as antibacterial, antihalitosis, antihyperuricemic, anti-implamation, antimicrobial, antioxidant, antiseptic, oral deodorant and many more. The bioactive components contained in kepel fruit (S. burahol) are phenolic compounds and flavonoid compounds. This review article will discuss the pharmacological activity and analysis of phytochemical compounds of kepel (S. burahol) against several diseases.